The Potential of Minipigs in the Development of Anticancer Therapeutics: Species Comparison and Examples of Special Applications. (April 2016) - Mahl, Andreas; Dincer, Zuhal; Heining, Peter
Minipigs are increasingly being used as an alternative to dog or monkey in nonclinical safety testing of pharmaceuticals since they share similar anatomical and physiological characteristics to humans. Integrative assessment of pharmacodynamic and pharmacokinetic data sets of drug candidates from in silico, in vitro, and in vivo investigations form the basis for selecting the most relevant nonrodent species for toxicology studies. Developing anticancer therapeutics represents a special challenge for species selection due to their effects on multiple organ systems. The toxicological profile of anticancer drugs can be associated with steep dose–response curves, especially due to dose-limiting toxicity on the alimentary, hematopoietic, and immune systems. Selection of an appropriate species for toxicology studies is of importance to avoid an inappropriately low (without benefit for the late-stage cancer patient) or high clinical starting dose (with a risk of unexpected adverse reactions). Although the minipig has been the preferred species to develop drugs applied topically, it is only rarely used in anticancer drug development compared to dog and monkey. In this context, we discuss the potential of minipigs in anticancer drug development with examples of programs for oral and dermal administration, intravascular application in drug-eluting stents, and local chemotherapy (chemoembolization).